2021
DOI: 10.1016/j.yebeh.2020.107497
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on seizure-related emergency attendances and hospital admissions — A territory-wide observational study

Abstract: This is a territory-wide study to investigate the impact of coronavirus disease 2019 (COVID-19) pandemic on Accident and Emergency Department (A&E) attendances and acute ward admissions for seizures. Adult patients who presented to the A&E with seizures from January 23, 2020 to March 24, 2020 (study period) were included and compared with parallel intervals from 2015 to 2019 (control periods). Preexisting time trend in control periods and potential changes during COVID-19 were analyzed by Poisson, negative and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 4 publications
2
14
0
Order By: Relevance
“…[3] The complete restriction of movement and assembly resulted in postponement of healthcare visits in Malaysia, similarly in many other countries. This unprecedented loss of access to healthcare is postulated to give rise to worsening seizure control and anxiety, which were reported in many countries in most continents, including China [4][5][6], Hong Kong [7], Pakistan [8] and Saudi Arabia [9] in Asia, Brazil [10] in South America, Spain [11,12] and Italy [13] in Europe, and United Stated of America. [14] However, most studies analyze mainly on the direct impact of AEDs on the psychological and clinical consequences, but not the access to emergency and outpatient services.…”
Section: Introductionmentioning
confidence: 99%
“…[3] The complete restriction of movement and assembly resulted in postponement of healthcare visits in Malaysia, similarly in many other countries. This unprecedented loss of access to healthcare is postulated to give rise to worsening seizure control and anxiety, which were reported in many countries in most continents, including China [4][5][6], Hong Kong [7], Pakistan [8] and Saudi Arabia [9] in Asia, Brazil [10] in South America, Spain [11,12] and Italy [13] in Europe, and United Stated of America. [14] However, most studies analyze mainly on the direct impact of AEDs on the psychological and clinical consequences, but not the access to emergency and outpatient services.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Walker et al demonstrated a significant overlap between the health queries about loss-of-smell globally with the onset of the COVID-19 pandemic [19] . Recent studies have shown a significant drop in acute admissions for seizures since the pandemic [20] , [21] . This is contrary to the predictions of increased seizure incidence because of acute mental stress, sleep deprivation, reduced access to healthcare and pharmacies, and drastic changes to clinical practice [20] , [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown a significant drop in acute admissions for seizures since the pandemic [20,21]. This is contrary to the predictions of increased seizures incidence because of acute mental stress, sleep deprivation, reduced access to healthcare and pharmacies, and drastic changes to clinical practice [20,22].…”
mentioning
confidence: 85%
“…[15][16][17][18][19] Although we cannot yet determine whether these psychological changes directly affect the public's visit behavior, many studies have found a shift in public behavior with anxiety over attending hospitals during the pandemic and associated with a significant reduction in ED presentations. [20][21][22][23][24] From the above data, we can conclude that the pandemic has changed people's behavioral patterns, especially the process of seeking medical care. These similar phenomena indicated that people might keep avoiding the hospital to the detriment of their health.…”
Section: Discussionmentioning
confidence: 99%
“…We further analyzed the clinical data of the patients who died in the ED. The APACHE II score of patients who died in the 2020 study period was slightly higher compared with that of 2019, which were 28 (IQR 18-35) and [19][20][21][22][23][24][25][26] respectively (p= 0.022). Whereas, the ED elapsed time dropped from 1.4 (IQR 0.2-4.8) days in 2019 to 0.2 in 2020 (IQR 0.1-1.2) (p=0.016) (Table 1).…”
Section: Clinical Characteristics Of Ed Deathmentioning
confidence: 98%